Mining Automobile Warranty Data - Chukova, Stefanka; Christozov, Dimitar (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Identifying the factors affecting cost of covering claims according to warranty policy is the main purpose of this study. The paper presents mining of automobile warranty data. Variability Driving Pattern was discovered as a factor having significant and sustainable impact on warranty cost.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 48-55